Thanks for trusting me, parent: Chinese pediatricians’ epistemic behaviour for trustworthiness in online medical consultations - Wang, Xueyu; Cao, Rujie (East Asian Pragmatics, 2023)
Despite an increasing scholarly interest in doctors’ behaviour in online settings, doctors’ epistemic behaviour (i.e. how doctor employs discursive practices to deal with their side and patients’ side knowledge) in online medical consultation (OMC) is still underexplored in research. Drawing on 300 highly rated OMC cases retrieved from dxy.com, a well-known digital health consulting platform in China, this study explores how Chinese pediatricians discursively deploy different types of epistemic behaviour in OMC settings. Data analyses yield three typical types of epistemic behaviour by Chinese pediatricians: strengthening epistemic primacy, mitigating epistemic certainty and showing concerns about parents’ epistemic domain. It is argued that pediatricians conduct epistemic behaviour to win parents’ perceptions of their trustworthiness. The three types of epistemic behaviour are targeted at the three dimensions of trustworthiness – ability, integrity, and benevolence. This study could yield insightful suggestions for online doctors’ strategic choice of discursive practices to promote a trusting doctor–patient relationship and harmonious consulting atmosphere in e-health activities.